Preparation method of high-transmittance wear-resistant nanoparticle composite polycarbonate film
By adding nanoparticles and antioxidants to the polycarbonate film and adopting a specific melt extrusion process, the problem of incomplete dispersion of nano-scale inorganic substances is solved, and a high light-transmitting and wear-resistant polycarbonate film is achieved, which improves the light-transmitting uniformity and quality of the film.
Patent Information
- Application Number
- CN202411778054.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-01
Smart Images

Figure BDA0005172017960000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thin films, and in particular to a method for preparing a highly light-transmitting, wear-resistant nanoparticle composite polycarbonate film. Background Art
[0002] Polycarbonate is referred to as PC, which has excellent properties in various aspects. Polycarbonate film or PC film is a film made of polycarbonate resin as the base material. It is famous for its excellent transparency, heat resistance, impact resistance, dimensional stability, non-toxicity, weather resistance, electrical insulation, radiation sterilization resistance and mechanical properties. It is a thermoplastic plastic with extremely excellent comprehensive properties. In addition, compared with organic glass acrylic and PMMA, which also have good comprehensive properties such as transparency, polycarbonate has the advantages of better impact resistance, low price and excellent flame retardancy.
[0003] When adding various inorganic substances to modify the existing polycarbonate films, they are usually added directly and then melt-blended and extruded. This addition method often causes incomplete dispersion of the inorganic substances in the film. In addition, if the selected inorganic substance is a nano-scale powder, the nano-scale powder will undergo secondary agglomeration during the blending and extrusion process. Ultimately, the excellent properties that nano-scale particles should have are not present, which has an adverse effect on the final performance of the film. Summary of the invention
[0004] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film.
[0005] The technical solution of the present invention is as follows:
[0006] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0007] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles and mixing, and adding an antioxidant to obtain a polycarbonate solution;
[0008] The preparation method of the nanoparticles is as follows:
[0009] The glass fiber is ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate is added dropwise, reacted for 6-10 hours, and then carbon quantum dots are added and heat treated to obtain the product;
[0010] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0011] The melt extrusion includes the following temperature sections:
[0012] The temperature of the first temperature control zone is 100-200℃, the temperature of the second temperature control zone is 200-250℃, the temperature of the third temperature control zone is 250-300℃, the temperature of the fourth temperature control zone is 250-300℃, and the fifth temperature control zone is 200-250℃; the screw speed is controlled at 10-45r / min.
[0013] Preferably, in step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 140-200° C. for 3-6 hours, cooling the solution to room temperature, centrifuging and drying.
[0014] Preferably, the mass ratio of citric acid, urea and water is 3-5:1:10-15.
[0015] Preferably, in step S1, the solvent is dichloromethane.
[0016] Preferably, in step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0017] Preferably, in step S1, the heat treatment is performed at a temperature of 300-500°C for 3-5 hours.
[0018] Preferably, in step S1, the added amount of the nanoparticles accounts for 3-6wt% of the polycarbonate powder.
[0019] Preferably, in step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate and carbon quantum dots is: 3-7:40-60:5-7:7-10:0.03-0.1.
[0020] Preferably, in step S2, the molecular weight of the polycarbonate powder is 10000-30000 expressed as viscosity average molecular weight.
[0021] The invention also discloses a highly light-transmitting and wear-resistant nano-particle composite polycarbonate film, which is prepared by any of the above-mentioned preparation methods.
[0022] The beneficial effects of the present invention are:
[0023] The invention discloses a method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film. By adding nanoparticles with wide-spectrum light-enhancing properties to the raw materials, the composite polycarbonate film has excellent light-transmitting effects in both the visible light and near-infrared light regions. The excellent wide-spectrum effect is combined with a specific melt extrusion process to provide a stronger heating effect of the characteristic frequency, and the extrusion molding effect is better. The crystallinity of the polycarbonate film is reduced during cooling, and the light-transmitting uniformity and quality of the film are greatly improved. Furthermore, the material formed into a rod-point structure with glass fiber has excellent hydrophobic and wear-resistant properties. Due to the specificity of the rod-point structure, the light-guiding property is greatly improved, thereby improving the light transmittance of the polycarbonate film. DETAILED DESCRIPTION
[0024] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0025] The polycarbonate resin of the following examples is a polymer in which dihydroxy compounds are bonded via carbonate bonds, and the molecular weight of the polycarbonate resin is 10,000-30,000 in terms of viscosity average molecular weight.
[0026] Example 1
[0027] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0028] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles to mix, and adding an antioxidant accounting for 1 wt % of the polycarbonate powder to obtain a polycarbonate solution;
[0029] The preparation method of the nanoparticles is as follows:
[0030] The glass fiber was ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate was added dropwise, reacted for 8 hours, and then carbon quantum dots were added and heat treated to obtain the product;
[0031] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0032] The melt extrusion includes the following temperature sections:
[0033] The temperature of the first temperature control zone is 150-180℃, the temperature of the second temperature control zone is 200-250℃, the temperature of the third temperature control zone is 250-280℃, the temperature of the fourth temperature control zone is 280-300℃, and the fifth temperature control zone is 200-250℃; the screw speed is controlled at 35r / min.
[0034] In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 160° C. for 4 hours, cooling the solution to room temperature, centrifuging and drying.
[0035] The mass ratio of the citric acid, urea and water is 3:1:12.
[0036] In step S1, the solvent is dichloromethane.
[0037] In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0038] In step S1, the heat treatment temperature is 400° C. and the treatment time is 4 hours.
[0039] In step S1, the added amount of the nanoparticles accounts for 3wt% of the polycarbonate powder.
[0040] In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate, and carbon quantum dots is 3:40:5:7:0.03.
[0041] In step S2, the molecular weight of the polycarbonate powder is 20,000 in terms of viscosity average molecular weight.
[0042] Example 2
[0043] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0044] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles to mix, and adding an antioxidant accounting for 1 wt % of the polycarbonate powder to obtain a polycarbonate solution;
[0045] The preparation method of the nanoparticles is as follows:
[0046] The glass fiber was ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate was added dropwise, reacted for 8 hours, and then carbon quantum dots were added and heat treated to obtain the product;
[0047] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0048] The melt extrusion includes the following temperature sections:
[0049] The temperature of the first temperature control zone is 180-200℃, the temperature of the second temperature control zone is 220-250℃, the temperature of the third temperature control zone is 280-300℃, the temperature of the fourth temperature control zone is 280-300℃, and the fifth temperature control zone is 230-250℃; the screw speed is controlled at 35r / min.
[0050] In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 180° C. for 5 hours, cooling the solution to room temperature, centrifuging and drying.
[0051] The mass ratio of the citric acid, urea and water is 4:1:13.
[0052] In step S1, the solvent is dichloromethane.
[0053] In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0054] In step S1, the heat treatment temperature is 400° C. and the treatment time is 4 hours.
[0055] In step S1, the added amount of the nanoparticles accounts for 4 wt % of the polycarbonate powder.
[0056] In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate, and carbon quantum dots is 5:49:6:7:0.05.
[0057] In step S2, the molecular weight of the polycarbonate powder is 20,000 in terms of viscosity average molecular weight.
[0058] Example 3
[0059] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0060] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles to mix, and adding an antioxidant accounting for 1 wt % of the polycarbonate powder to obtain a polycarbonate solution;
[0061] The preparation method of the nanoparticles is as follows:
[0062] The glass fiber was ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate was added dropwise, reacted for 8 hours, and then carbon quantum dots were added and heat treated to obtain the product;
[0063] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0064] The melt extrusion includes the following temperature sections:
[0065] The temperature of the first temperature control zone is 170-190℃, the temperature of the second temperature control zone is 210-230℃, the temperature of the third temperature control zone is 270-300℃, the temperature of the fourth temperature control zone is 260-300℃, and the fifth temperature control zone is 230-250℃; the screw speed is controlled at 45r / min.
[0066] In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 160° C. for 5 hours, cooling the solution to room temperature, centrifuging and drying.
[0067] The mass ratio of the citric acid, urea and water is 5:1:13.
[0068] In step S1, the solvent is dichloromethane.
[0069] In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0070] In step S1, the heat treatment temperature is 400° C. and the treatment time is 5 hours.
[0071] In step S1, the added amount of the nanoparticles accounts for 6wt% of the polycarbonate powder.
[0072] In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate, and carbon quantum dots is 4:60:7:7:0.06.
[0073] In step S2, the molecular weight of the polycarbonate powder is 20,000 in terms of viscosity average molecular weight.
[0074] Example 4
[0075] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0076] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles to mix, and adding an antioxidant accounting for 1 wt % of the polycarbonate powder to obtain a polycarbonate solution;
[0077] The preparation method of the nanoparticles is as follows:
[0078] The glass fiber was ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate was added dropwise, reacted for 8 hours, and then carbon quantum dots were added and heat treated to obtain the product;
[0079] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0080] The melt extrusion includes the following temperature sections:
[0081] The temperature of the first temperature control zone is 160-180℃, the temperature of the second temperature control zone is 230-250℃, the temperature of the third temperature control zone is 250-300℃, the temperature of the fourth temperature control zone is 250-300℃, and the fifth temperature control zone is 200-230℃; the screw speed is controlled at 45r / min.
[0082] In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 160° C. for 4 hours, cooling the solution to room temperature, centrifuging and drying.
[0083] The mass ratio of the citric acid, urea and water is 5:1:15.
[0084] In step S1, the solvent is dichloromethane.
[0085] In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0086] In step S1, the heat treatment temperature is 400° C. and the treatment time is 4 hours.
[0087] In step S1, the added amount of the nanoparticles accounts for 6wt% of the polycarbonate powder.
[0088] In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate, and carbon quantum dots is 7:50:7:10:0.1.
[0089] In step S2, the molecular weight of the polycarbonate powder is 20,000 in terms of viscosity average molecular weight.
[0090] Example 5
[0091] The method for preparing a highly light-transmitting and wear-resistant nanoparticle composite polycarbonate film comprises the following steps:
[0092] S1: dissolving polycarbonate powder in a solvent, adding nanoparticles to mix, and adding an antioxidant accounting for 1 wt % of the polycarbonate powder to obtain a polycarbonate solution;
[0093] The preparation method of the nanoparticles is as follows:
[0094] The glass fiber was ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate was added dropwise, reacted for 8 hours, and then carbon quantum dots were added and heat treated to obtain the product;
[0095] S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film;
[0096] The melt extrusion includes the following temperature sections:
[0097] The temperature of the first temperature control zone is 100-200℃, the temperature of the second temperature control zone is 200-250℃, the temperature of the third temperature control zone is 250-300℃, the temperature of the fourth temperature control zone is 250-300℃, and the fifth temperature control zone is 200-250℃; the screw speed is controlled at 35r / min.
[0098] In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 200° C. for 3 h, cooling the solution to room temperature, centrifuging and drying.
[0099] The mass ratio of the citric acid, urea and water is 5:1:14.
[0100] In step S1, the solvent is dichloromethane.
[0101] In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
[0102] In step S1, the temperature of the heat treatment is 400°C, treatment 3.
[0103] In step S1, the added amount of the nanoparticles accounts for 3-6wt% of the polycarbonate powder.
[0104] In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate, and carbon quantum dots is 6:50:6:9:0.08.
[0105] In step S2, the molecular weight of the polycarbonate powder is 20,000 in terms of viscosity average molecular weight.
[0106] Comparative Example 1
[0107] Different from Example 2, no nanoparticles were added.
[0108] Comparative Example 2
[0109] The difference from Example 2 is that glass fiber is not added. Specifically, ethanol and ammonia water are mixed, tetraethyl orthosilicate is added dropwise, and the reaction is carried out for 8 hours. Then, carbon quantum dots are added and heat treated to obtain the product.
[0110] Comparative Example 3
[0111] The difference from Example 2 is that no carbon quantum dots are added. Specifically, the glass fiber is ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate is added dropwise, reacted for 8 hours, and heat treated to obtain the product.
[0112] Comparative Example 4
[0113] Different from Example 2, the melt extrusion includes the following temperature sections:
[0114] The temperature of the first temperature control zone is 200-300℃, the temperature of the second temperature control zone is 200-300℃, the temperature of the third temperature control zone is 200-300℃, the temperature of the fourth temperature control zone is 200-300℃, and the fifth temperature control zone is 200-300℃; the screw speed is controlled at 35r / min.
[0115] The performance of the above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0116] Table 1 Performance test results of examples and comparative examples
[0117]
[0118] As can be seen from the above table, the performance of the embodiment is better than that of the comparative example. The main reasons may be as follows: from the analysis of comparative examples 1-4, it can be seen that the embodiment has excellent light transmission effect in both visible light and near-infrared light regions by adding nanoparticles with wide spectrum enhanced light transmission into the raw materials, and its excellent wide spectrum effect combined with the specific melt extrusion process makes it have a stronger heating effect of the characteristic frequency, and the extrusion molding effect is better. In addition, the crystallinity of the polycarbonate film is reduced during cooling, which greatly improves the light transmission uniformity and quality of the film. Furthermore, the material formed into a rod-point structure with glass fiber has excellent hydrophobic and wear-resistant properties. Due to the specificity of the rod-point structure, the light guiding property is greatly improved, thereby improving the stability of the polycarbonate film.
[0119] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all these changes and deformations should fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a highly transparent and wear-resistant nanoparticle composite polycarbonate film, characterized in that: The following steps are involved: S1: dissolving polycarbonate powder in a solvent, adding nanoparticles and mixing, and adding an antioxidant to obtain a polycarbonate solution; The preparation method of the nanoparticles is as follows: The glass fiber is ultrasonically dispersed in ethanol and ammonia water, ethyl orthosilicate is added dropwise, reacted for 6-10 hours, and then carbon quantum dots are added and heat treated to obtain the product; S2: After the polycarbonate solution is evaporated and degassed, it is melted and extruded and rolled into a film; The melt extrusion includes the following temperature sections: The temperature of the first temperature control zone is 100-200℃, the temperature of the second temperature control zone is 200-250℃, the temperature of the third temperature control zone is 250-300℃, the temperature of the fourth temperature control zone is 250-300℃, and the fifth temperature control zone is 200-250℃; the screw speed is controlled at 10-45r / min.
2. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the preparation method of the carbon quantum dots is as follows: dissolving citric acid and urea in water to obtain a mixed solution, then heating the mixed solution at 140-200° C. for 3-6 hours, cooling the solution to room temperature, centrifuging and drying.
3. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 2, characterized in that: The mass ratio of the citric acid, urea and water is 3-5:1:10-15.
4. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the solvent is dichloromethane.
5. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the antioxidant is 2,2'-methylenebis(4-methyl-6-tert-butylphenol).
6. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the heat treatment temperature is 300-500°C and the treatment time is 3-5h.
7. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the added amount of the nanoparticles accounts for 3-6wt% of the polycarbonate powder.
8. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S1, the mass ratio of the glass fiber, ethanol, ammonia water, tetraethyl orthosilicate and carbon quantum dots is: 3-7:40-60:5-7:7-10:0.03-0.
1.
9. The method for preparing the highly transparent and wear-resistant nanoparticle composite polycarbonate film according to claim 1, characterized in that: In step S2, the molecular weight of the polycarbonate powder is 10,000-30,000 in terms of viscosity average molecular weight.
10. Highly transparent and wear-resistant nanoparticle composite polycarbonate film, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
Method for preparing polycarbonate sheet
CN120554680A